2016
DOI: 10.1111/jop.12421
|View full text |Cite
|
Sign up to set email alerts
|

Odontogenic myxoma: a clinicopathological study in a South African population

Abstract: BACKGROUND: Odontogenic myxoma is a benign, locally aggressive neoplasm of the jaws. Prevalence rates range between 0.5% and 17.7% of odontogenic tumours. There are few reports in the literature on this lesion in African populations, and therefore, this study aimed to report on odontogenic myxoma in a South African population over a 40-year period. METHODS: The clinical records and orthopantomograms of 29 histopathologically diagnosed odontogenic myxoma were retrospectively analysed. Details of age, gender, et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
37
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(51 citation statements)
references
References 20 publications
(44 reference statements)
7
37
0
7
Order By: Relevance
“…Radiologically, these residual bony trabeculae and dense fibrous tissue manifested as septa in multilocular OMs. 8 As reported previously, fine and straight septa separated the lesion into triangular, square or rectangular compartments, which are described as "honeycomb" or "tennis racket". 3,6,8,11 These features significantly aided in the proper diagnosis of OM.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Radiologically, these residual bony trabeculae and dense fibrous tissue manifested as septa in multilocular OMs. 8 As reported previously, fine and straight septa separated the lesion into triangular, square or rectangular compartments, which are described as "honeycomb" or "tennis racket". 3,6,8,11 These features significantly aided in the proper diagnosis of OM.…”
Section: Discussionmentioning
confidence: 90%
“…8 As reported previously, fine and straight septa separated the lesion into triangular, square or rectangular compartments, which are described as "honeycomb" or "tennis racket". 3,6,8,11 These features significantly aided in the proper diagnosis of OM. In this present study, only 10 multilocular OMs showed that typical appearance, and the remaining 5 demonstrated fewer septa.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations